Tandem Mass Spectrometric Analysis of Glycopeptides Derived from the Tryptic Digestion of Human Chorionic Gonadotropin (hCG) - L.H, Gam; Latiff, Aishah (Malaysian Journal of Science, 2006)
Analysis of hCG glycopeptides by ion trap mass spectrometer is difficult due to ion suppression effect attributed to the sugar components of glycopeptides. In addition, collision induced dissociation of glycopeptides also could not provide useful product ion spectrum. In our present study, determination of amino acid sequences of hCG glycopeptides was accomplished by enzymatic deglycosylation prior to tandem mass spectrometric analysis. Enzymatic deglycosylation was found more effective when performed on short stranded tryptic fragments compared to its intact molecule. Deglycosylated-peptides display greater resistance to collision induced dissociation compared to peptides, which revealed higher collision energy required for fragmentation.